NEW BRAINS FOR THE DEFENCE SYSTEM : Systematic view on the Finnish Defence Forces on the edge of Artificial Intelligence revolution - Hemminki, Petteri (My University, 2020)
There are about 3,5 billion smartphones in the world, and all users can use applications based on the research of Artificial Intelligence. The rapid expansion of this research to the new areas creates both new threats and possibilities for the defence systems in the future. The Finnish Defence Forces is obligated to plan, implement, and maintain ade-quate military capabilities for all risk dimensions, and an essential question is raised, how to prepare the whole defence system for the future development of Artificial Intelligence as an emerging research area. To answer this question, the Soft System Methodology is chosen for the main method of this study. This methodology is suitable for the future studies, when the area of study is complex, organized, self-regulating, dynamic, and in interaction with its environment. This provides a needed holistic approach to the defence system along with a foresight perspective. The other method, document analysis is focusing on the open sources and used to study the characteristics of the defense system and the history of technological development. The third method, deductive reasoning, is used especially in model creation and risk analysis. As a result, this study presents five recommendations for the organization: - the organization should increase the intensity of collecting data - the organization should improve the capability to store and share data - the organization should boost the training of agile methods with the experimental projects - the organization should tune-up organizational culture to match the future - the organization should keep on monitoring the development of AI The research results can be summarized in the following conclusion: it is important to choose the role we want to play in this potential Artificial Intelligence revolution - today’s decisions matter the most for the future.

Maailmassa on noin 3,5 miljardia älykännykkää, joissa voidaan käyttää applikaatioita, jotka perustuvat tekoälytutkimukseen. Tämän tekoälytutkimuksen nopea leviäminen uusille alueille luo uusia uhkia ja mahdollisuuksia puolustusjärjestelmille tulevaisuudessa. Suomen Puolustusvoimilla on velvoite suunnitella, rakentaa ja ylläpitää riittäviä sotilaallisia suorituskykyjä kaikkia uhkaulottuvuuksia varten, mikä herättää kysymyksen siitä, miten koko puolustusjärjestelmän tulisi varautua tulevaisuuteen nopeasti kehittyvän tekoälytutkimuksen takia. Tässä tutkimuksessa esitettyyn kysymykseen vastataan pehmeän systeemimetodologian avulla, joka on valittu tutkimuksen päämetodiksi. Se soveltuu tulevaisuuden tutkimuksen menetelmäksi, kun tutkittava alue on monimutkainen, organisoitu, it-sesäätelevä, dynaaminen ja vuorovaikutteinen ympäristönsä kanssa. Tämä mahdollistaa puolustusjärjestelmän lähestymisen kokonaisvaltaisella ja tulevaisuuden näkökulman säilyttävällä tavalla. Toinen käytettävä metodi, avoimiin lähteisiin perustuva kirjallisuustutkimus, keskittyy tutkimuksessa puolustusjärjestelmän ominaispiirteisiin ja teknologisen kehityksen historiaan. Kolmatta metodia, deduktiivista päättelyä, käytetään erityisesti mallien luomisessa ja riskien analysoinnissa. Tutkimustuloksena esitetään organisaatiolle seuraavia suosituksia: - organisaation tulisi panostaa datan keräämisen tehokkuuteen - organisaation tulisi parantaa kykyä tallentaa ja jakaa dataa - organisaation tulisi tehostaa harjaantumista ketteriin menetelmiin kokeiluluonteisilla projekteilla - organisaation tulisi virittää organisaatiokulttuuriaan vastaamaan tulevaisuutta - organisaation tulisi jatkaa tekoälyn kehittymisen seurantaa Tutkimustulokset voidaan tiivistää seuraavaan johtopäätökseen: on tärkeää päättää, missä roolissa haluamme kohdata tulevaisuudessa mahdollisen tekoälyn vallankumouksen - tämän päivän päätöksillä on kaikkein tärkein merkitys tulevaisuuden kannalta.
Keywords: Artificial Intelligence, Soft System Methodology, defence, system, future